(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the knowledge and attitudes of nurses at American International Hospital regarding pediatric cardiopulmonary resuscitation (CPR) and to identify associated factors. Methods: A cross-sectional descriptive study was conducted from August 2024 to January 2025 on 105 nurses. Knowledge and attitudes were assessed using a standardized questionnaire. Results: The rates of nurses with good knowledge and attitudes towards pediatric CPR were 38.1% and 40%, respectively. Good knowledge was associated with higher education levels (p=0.036). Knowledge gaps were identified in initial management of suspected cardiac arrest, chest compression techniques, artificial respiration, and compression/ventilation ratios. Negative attitudes were observed regarding the use of automated external defibrillators and mouth-to-mouth resuscitation. Conclusion: Nurses’ knowledge and attitudes regarding pediatric CPR are limited. Enhanced training and education, particularly in defibrillator use and practical skills, are needed to improve CPR outcomes in children.